1995
DOI: 10.1074/jbc.270.3.1113
|View full text |Cite
|
Sign up to set email alerts
|

Existence of Branched Side Chains in the Cell Wall Mannan of Pathogenic Yeast, Candida albicans

Abstract: Isolation of side chain oligosaccharides from mannans of Candida albicans NIH B-792 (serotype B) and Candida parapsilosis IFO 1396 strains has been conducted by acetolysis under mild conditions. Structural study of these oligosaccharides by 1H and 13C NMR and methylation analyses indicated the presence of novel branched side chains with the following structures in C. albicans mannan. [sequence: see text] It was observed that the H-1 proton chemical shifts of the second and the third mannose units from the redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(96 citation statements)
references
References 56 publications
2
88
0
Order By: Relevance
“…These organisms contain mannan-like cell wall glycans, although the side branches are highly variable between species, and for Candida it has been shown that an Mnn9p homologue is involved in mannan synthesis (55)(56)(57)(58). Although Mnn9p-containing protein complexes in these species have not so far been reported, it seems likely that the mechanisms that determine which proteins receive mannan in S. cerevisiae will be conserved in other yeasts and fungi.…”
Section: Discussionmentioning
confidence: 99%
“…These organisms contain mannan-like cell wall glycans, although the side branches are highly variable between species, and for Candida it has been shown that an Mnn9p homologue is involved in mannan synthesis (55)(56)(57)(58). Although Mnn9p-containing protein complexes in these species have not so far been reported, it seems likely that the mechanisms that determine which proteins receive mannan in S. cerevisiae will be conserved in other yeasts and fungi.…”
Section: Discussionmentioning
confidence: 99%
“…The anomeric proton chemical shifts of oligosaccharides were assigned by adapting the findings of Shibata et al (1993Shibata et al ( , 1995 …”
Section: 'H-nmr Spectrum Of the Mannoproteinmentioning
confidence: 99%
“…C. albicans is a dimorphic fungus which can alternate between yeast and hyphal phases, depending on the growth conditions (Blasi et al, 1994). The cell wall of C. albicans contains a mannan which has a linear 1,6-a-linked mannose backbone with side chains of 1,2-a-, 1,2-p-and 1J-a-linked mannose units (Shibata et al, 1995). The antigenicity of Candida species depends on the structure of their mannans, and differences of antigenicity in mannans are used in the classification of Candida species (Ataoglu et al, 1993;Kobayashi et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…This nonempirical assignment method has been demonstrated to give satisfactory results (8,18,24,25,31). The H-1 signal of the reducing terminal ␣-mannose unit (␦ ϭ ϳ5.35 ppm) was able to be empirically assigned.…”
Section: Resultsmentioning
confidence: 99%
“…1 based on the results obtained by the structural analysis of C. guilliermondii mannan (18) and the substrate specificity of an ␣-1,6-mannosyltransferase of C. albicans (23) responsible for the formation of the branched oligosaccharides corresponding to factor 4 (24,25). Namely, the introduction of a ␤-1,2-linked mannose unit from GDP-mannose to the nonreducing terminal ␣-1,3-linked mannose unit of an ␣-linked mannopentaosyl side chain, Man␣133(Man␣136)Man␣132Man␣132Man, synthesized from Man␣133Man␣132Man␣132Man corresponding to factor 34 (26), takes place by participation of the ␤-1,2-mannosyltransferase IV, and then, the elongation of a ␤-1,2-linked one to a resulting product, Man␤132Man␣133-(Man␣136)Man␣132Man␣132Man, takes place by participation of the ␤-1,2-mannosyltransferase V in succession.…”
mentioning
confidence: 99%